Measuring Cybersecurity Awareness in a South African Military Sample - Bester, Kyle John; Arendse, Danille (Scientia Militaria - South African Journal of Military Studies, 2024)
Cyberspace has been identified as a new domain of warfare; awareness of cyber threats is therefore crucial for members of the military because it allows for greater insight into potential cyber threats and attacks. Furthermore, developing cybersecurity awareness may assist in the detection of cyber threats in the workplace, and may further assist members of the military to be cognisant of their own vulnerability in cyberspace. In South Africa, cybersecurity is a topic of interest, and the South African National Defence Force has highlighted the need to enhance its cybersecurity capacity. The Cybersecurity Orientation Questionnaire was developed for members of the South African military with the fundamental objective of assessing their cybersecurity awareness as part of a larger study. The purpose of the study on which this article is based, was to explore the initial validation of the Questionnaire using a South African military sample. The study design was quantitative, and the reliability and factor structure of the Questionnaire were analysed by means of the Statistical Package for the Social Sciences. The sample size consisted of 182 military participants who were based at two military educational institutions. The Questionnaire showed acceptable reliability for research purposes (r = .79; p = .000) and the prominent three-factor structure was in line with the theorised factors envisioned during the development of the Questionnaire. Initial validation of the Questionnaire showed promising results for assessing cybersecurity awareness in the South African military sample. This study therefore emphasises the importance of developing instruments specifically for the South African military context.